Dengue vaccine design : issues and challenges - Cardosa, Mary Jane (The British Council, 1998)
Dengue virus infection is now a global problem affecting tens of millions of people. The spread of the four dengue virus serotypes had led to increased incidence of dengue haemorrhagic fever (DHF) reported and with 2.5 billion people at risk, efforts towards the development of safe and effective vaccines against dengue must be accelerated. This chapter reviews some of the important lessons of pathogenesis which may be learnt from classical studies in the field and place these in the context of current knowledge about the molecular biology of the virus. The issues which have to be addressed in designing a safe vaccine against dengue are raised and the problems of designing subunit as well as whole virus vaccines are pointed out, particularly with regard to the phenomenon of antibody dependent enhancement and, more generally, the problem of immune potentiation of disease. More efforts must be made to understand the basis of pathogenesis in DHF and in finding out what nature has to teach about protection against and recovery from dengue virus infection.